Microbial molecules, metabolites, and malignancy - Ryan M. Thomas (Neoplasia: An International Journal for Oncology Research)
Research elucidating the role of the microbiome in carcinogenesis has grown exponentially over the past decade. Initially isolated to associative studies on colon cancer development, the field has expanded to encompass nearly every solid and liquid malignancy that may afflict the human body. Investigations are rapidly progressing from association to causation and one particular area of causal effect relates to microbial metabolites and how they influence cancer development, progression, and treatment response. These metabolites can be produced de novo from individual members of the microbiome, whether that be bacteria, fungi, archaea, or other microbial organisms, or they can be through metabolic processing of dietary compounds or even host-derived molecules. In this review, contemporary research elucidating mechanisms whereby microbial-derived molecules and metabolites impact carcinogenesis and cancer treatment efficacy will be presented. While many of the examples focus on bacterial metabolites in colon carcinogenesis, this simply illustrates the accelerated nature of these investigations that occurred early in microbiome research but provides an opportunity for growth in other cancer areas. Indeed, research into the interaction of microbiome-derived metabolites in other malignancies is growing as well as investigations that involve non-bacterial metabolites. This review will provide the reader a framework to expand their knowledge regarding this complex and exciting field of cancer research.